Pekerja Anak dan Goncangan Pertanian di Indonesia - Kharisma, Bayu (Jurnal Ekonomi Kuantitatif Terapan, 2017)
The aims of this research is to determine the effect of crop loss shocks against child labor and the role of the assets held by households, both farm and non-farm business can reduce the impact of these shocks. The results showed that the effects of crop loss shocks insignificantly affect child labor at the age of 5-14 years. This indicates that in the event of crop loss shocks, households do not use a coping strategy by increasing child labor to dampen the shocks. Meanwhile, assets used for non-farm business was able to reduce the demand for child labor. On the other hand, farm business assets has positive effect on working children aged 5-14. This indicates the wealth effect phenomenon that occurred in Indonesia.
Keywords: bencana gagal panen, pekerja anak, aset farm business, non farm business, wealth effect